2003
DOI: 10.1038/nature01679
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution drives divergence of a hybrid inviability gene between two species of Drosophila

Abstract: Speciation--the splitting of one species into two--occurs by the evolution of any of several forms of reproductive isolation between taxa, including the intrinsic sterility and inviability of hybrids. Abundant evidence shows that these hybrid fitness problems are caused by incompatible interactions between loci: new alleles that become established in one species are sometimes functionally incompatible with alleles at interacting loci from another species. However, almost nothing is known about the genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
328
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(338 citation statements)
references
References 40 publications
9
328
0
1
Order By: Relevance
“…Indeed, consistent with the idea that genomic conflict is a common phenomenon, detailed analysis of hybrids showed that ''speciation'' genes tend to be involved in intragenomic conflict, but their effect could be only detected in hybrids (Perez et al 1993;Dermitzakis et al 2000;Tao et al 2001;Presgraves et al 2003;Phadnis and Orr 2009;Tang and Presgraves 2009).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, consistent with the idea that genomic conflict is a common phenomenon, detailed analysis of hybrids showed that ''speciation'' genes tend to be involved in intragenomic conflict, but their effect could be only detected in hybrids (Perez et al 1993;Dermitzakis et al 2000;Tao et al 2001;Presgraves et al 2003;Phadnis and Orr 2009;Tang and Presgraves 2009).…”
mentioning
confidence: 74%
“…CG11943, a homolog of the human NUP205 gene, shows strong evidence of ongoing selection in D. mauritiana and D. simulans. Presgraves et al (2003) and Tang and Presgraves (2009) previously identified Nup96 and Nup160 as one cause of hybrid lethality between D. simulans and D. melanogaster, due to an interaction with an as-yetunidentified X-linked factor. Given that CG11943 is located on the X chromosome, we speculate that it may be an alternative interaction partner of Nup160 and/or Nup96 instead of (or in addition to) their suggested Nup153.…”
Section: Nucleoporins As a Preferential Target For Positive Selectionmentioning
confidence: 99%
“…Although the recent speciation literature has appropriately emphasized the role of selection in the development of reproductive isolation (19)(20)(21)(22), the present study provides a possible counterexample; because of selfing, genetic drift could provide an efficient means for the accumulation of hybrid incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although selection on leaf size has not been directly assessed for Antirrhinum, species with small leaves (e.g., A. charidemi, A. microphyllum, and A. mollisimum) are found in the driest habitats encountered by the group, consistent with water limitation playing a role. Moreover, all seven QTL influencing values of PC1, the PC with the major effect on leaf area, act in the same direction as that of the parental difference, consistent with their having been subject to directional selection (30)(31)(32). The expected directions of size selection can be visualized in allometric space as vectors with major components at right angles to (normal to) the area isosurfaces ( Fig.…”
Section: Discussionmentioning
confidence: 99%